Pheochromocytoma and Paraganglioma Patients With Poor Survival Often Show Brown Adipose Tissue Activation - Abdul Sater, Zahraa (J Clin Endocrinol Metab, 2020)
CONTEXT: Pheochromocytomas/paragangliomas (PPGLs) are neuroendocrine tumors that can secrete norepinephrine (NE). Brown adipose tissue (BAT) activation is mediated through the action of NE on β-adrenoceptors (β-ARs). In some malignancies, BAT activation is associated with higher cancer activity. OBJECTIVE: To study the relationship between BAT activation and PPGL clinical outcomes. DESIGN: A retrospective case-control study that included 342 patients with PPGLs who underwent (18)F-fluoro-2-deoxy-D-glucose positron emission tomography-computed tomography ((18)F-FDG PET/CT) imaging at the National Institutes of Health (NIH). We excluded all patients with parasympathetic tumors and those who underwent (18)F-FDG PET/CT after PPGL resection. Scans of 205 patients were reviewed by 2 blinded nuclear medicine physicians; 16 patients had BAT activation on (18)F-FDG PET/CT [7.80%; age 27.50 (15.00–45.50) years; 10 female/6 male; body mass index [BMI] 24.90 [19.60–25.35] kg/m(2)). From the remaining 189 patients, we selected 36 matched controls (age 34.4 [25.4–45.5] years; 21 female/15 male; BMI 25.0 [22.0–26.0] kg/m(2)). PRIMARY OUTCOME MEASURE: Overall survival. RESULTS: The presence of active BAT on (18)F-FDG PET/CT was associated with decreased overall survival when compared with the control group (HRz 5.80; 95% CI, 1.05–32.05; P = 0.02). This association remained significant after adjusting for the SDHB mutation. Median plasma NE in the BAT group was higher than the control group [4.65 vs 0.55 times above the upper limit of normal; P < 0.01]. There was a significant association between higher plasma NE levels and mortality in PPGLs in both groups. CONCLUSIONS: Our findings suggest that the detection of BAT activity in PPGL patients is associated with higher mortality. We suggest that BAT activation could either be reflecting or contributing to a state of increased host stress that may predict poor outcome in metastatic PPGL.